2021
DOI: 10.3390/nu13082637
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccines in Children with Cow’s Milk and Food Allergies

Abstract: The COVID-19 pandemic is the most challenging global health crisis of our times. Vaccination against COVID-19 plays a key role to control the current pandemic situation. The risk of allergic reactions to new COVID-19 vaccines is low. However, there is a debate on the safety in allergic patients following post marketing findings by different agencies. Our aim is to understand from current experiences whether children with cow’s milk or food allergy are at higher risk than a general population for allergic react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Other studies have shown that full vaccination of two or three doses of RNA vaccine can significantly increase the level of neutralizing antibodies in the recipients, preventing the occurrence of a global pandemic amid the frequent emergence of new variants of SARS-CoV-2 both in adults and children [45] , [48] , [108] , [109] , [110] , [111] , [112] , [113] . Robust clinical data also confirmed that the COVID-19 vaccine is safe in children with specific diseases, including congenital immunodeficiency, congenital heart disease, pediatric inflammatory bowel disease and allergy [114] , [115] , [116] , [117] , [118] , [119] , [120] , [121] , [122] . Given that some parents are still hesitant about vaccine safety, reducing the single-dose volume of vaccines for children and extending the vaccination interval has been proven to reduce the occurrence of adverse events, which is expected to become the vaccination strategy for children in the future [111] , [123] , [124] .…”
Section: Why Children Should Be Vaccinated Against Covid-19?mentioning
confidence: 74%
“…Other studies have shown that full vaccination of two or three doses of RNA vaccine can significantly increase the level of neutralizing antibodies in the recipients, preventing the occurrence of a global pandemic amid the frequent emergence of new variants of SARS-CoV-2 both in adults and children [45] , [48] , [108] , [109] , [110] , [111] , [112] , [113] . Robust clinical data also confirmed that the COVID-19 vaccine is safe in children with specific diseases, including congenital immunodeficiency, congenital heart disease, pediatric inflammatory bowel disease and allergy [114] , [115] , [116] , [117] , [118] , [119] , [120] , [121] , [122] . Given that some parents are still hesitant about vaccine safety, reducing the single-dose volume of vaccines for children and extending the vaccination interval has been proven to reduce the occurrence of adverse events, which is expected to become the vaccination strategy for children in the future [111] , [123] , [124] .…”
Section: Why Children Should Be Vaccinated Against Covid-19?mentioning
confidence: 74%
“…Vaccination is considered the best advisable strategy to prevent COVID-19 infection. Until now, immunization is available for people aged 5 years and older and it demonstrated either a good efficacy or an acceptable security profile [ 90 , 91 ]. Starting from 2021, in the pediatric age, immunization is actually offered by a Messenger RNA vaccine shot in the muscle of the upper arm.…”
Section: Methodsmentioning
confidence: 99%
“…Most international documents suggest [ 7 , 9 11 , 20 ] to proceed with vaccination as normal (in the green zone). However, considering that some patients who developed allergic reactions after BNT162b2 vaccine have a previous history of food anaphylaxis [ 21 23 ] we suggest performing the vaccine in vaccination centers equipped for anaphylaxis management [ 6 , 24 ]. Idiopathic anaphylaxis and exercise-induced anaphylaxis.…”
Section: Introductionmentioning
confidence: 99%